A Strongly Convergent Method for the Split Feasibility Problem - Yonghong Yao; Yeong-Cheng Liou; Naseer Shahzad (Abstract and Applied Analysis)
The purpose of this paper is to introduce and analyze a strongly convergent method which combined regularized method, with extragradient method for solving the split feasibility problem in the setting of infinite-dimensional Hilbert spaces. Note that the strong convergence point is the minimum norm solution of the split feasibility problem.